Forging New Narratives. (August 2022) - Ben-Meir, Nirit Binyamini; Dudek, Laura; Tomica,; Wilson, Arthur
Visualizing information is a process of exposure. All data tells a story. The science and art of information design lies in choosing which one to tell—and how to get others to listen.